2012
DOI: 10.1103/physrevb.86.024425
|View full text |Cite
|
Sign up to set email alerts
|

Towards high-frequency negative permeability using magnonic crystals in metamaterial design

Abstract: We investigate the magnonic properties of thin slabs of one-dimensional magnonic crystals with the aim of obtaining a structure that possesses negative permeability at high frequencies. Metamaterials of this kind could be used within devices based on the negative refractive index phenomenon. We calculate the relative excitation strengths of different spin-wave modes in one-dimensional magnonic crystals. We find that the coupling between light and high-order magnonic modes can be significant for the specific de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…For plasmonics, the characteristic length scales of features are in the millimetre to micrometre range. One important area to be explored is the incorporation of magnetically polarisable elements in a plasmonic array in order to tune different properties such as negative refraction with external applied fields [91,[190][191][192]. Further directions include laser induced switching [193], coupling light to charge and spin currents for information encoding and transfer, optical trapping and manipulation, nanoplasmonics and imaging, to name just a few, with the potential to generate and steer spinwaves in an all optical set-up [194].…”
Section: Discussionmentioning
confidence: 99%
“…For plasmonics, the characteristic length scales of features are in the millimetre to micrometre range. One important area to be explored is the incorporation of magnetically polarisable elements in a plasmonic array in order to tune different properties such as negative refraction with external applied fields [91,[190][191][192]. Further directions include laser induced switching [193], coupling light to charge and spin currents for information encoding and transfer, optical trapping and manipulation, nanoplasmonics and imaging, to name just a few, with the potential to generate and steer spinwaves in an all optical set-up [194].…”
Section: Discussionmentioning
confidence: 99%
“…The results presented in this paper allow us to speculate that if this material in which the magnonic amplitude is concentrated is in addition characterized by a low damping coefficient, then the resonance will be even stronger and the quality factor will be even higher than that obtained in Ref. 37. A rigorous proof of this hypothesis is however beyond the present study.…”
Section: Application Of the Proposed Three-dimensional Magnonic Crmentioning
confidence: 46%
“…37,Mruczkiewicz et al showed that stacks of 2D all-ferromagnetic magnonic crystals could be used to design metamaterials with negative permeability at frequencies of several tenths of GHz. In particular, negative permeability was observed in the vicinity of high-order resonances for which the magnonic mode amplitude was preferentially distributed within one of the two constituent materials.…”
Section: Application Of the Proposed Three-dimensional Magnonic Crmentioning
confidence: 99%
“…Magnetic materials with periodic modulation are called magnonic crystals (MCs) 1,2,3 . Presently, MCs get particular interest due to the possibility of tailoring frequency spectra of SWs at the nanoscale; as a consequence, it is possible to understand magnetization dynamics and: a) to design metamaterial devices 4,5 , b) to transduce and transmit signals 6,7,8 , c) to realize magnonic transistors 9 , d) to make logic operations 10,11,12 .…”
Section: Introductionmentioning
confidence: 99%